Toward a Symptom-Guided Neurostimulation for Gilles de la Tourette Syndrome - Pedroarena-Leal, Nicole; Ruge, Diane (Frontiers in Psychiatry, 2017)
Therapy resistance of approximately one-third of patients with Gilles de la Tourette syndrome (GTS) requires consideration of alternative therapeutic interventions. The article provides a condensed review of the invasive and non-invasive stimulation techniques that have been applied, to date, for treatment and investigation of GTS. Through this short review, the article discusses potential novel applications for neurostimulation techniques based on a symptom-guided approach. The concept of considering the physiological basis of specific symptoms when using stimulation techniques will provide a platform for more effective non-pharmacological neuromodulation of symptoms in GTS.